Answer: [tex]-3\sqrt{5}[/tex]
-3 times the square root of 5
=============================================
Explanation:
Let [tex]x = \sqrt{5}[/tex]
Replace all the root 5 terms with x and we go from
[tex]3\sqrt{5}-8\sqrt{5}+2\sqrt{5}[/tex]
to
[tex]3x-8x+2x[/tex]
From here, combine like terms to get
[tex]3x-8x+2x = -5x+2x = -3x[/tex]
and the last thing to do is replace the x with sqrt(5)
[tex]-3x = -3\sqrt{5}[/tex]
Meaning that,
[tex]3x-8x+2x = -3x[/tex]
[tex]3\sqrt{5}-8\sqrt{5}+2\sqrt{5} = -3\sqrt{5}[/tex]